The P-site A76 2′-OH acts as a peptidyl shuttle in a stepwise peptidyl transfer mechanism1. Issue 32 (10th April 2015) - Monajemi, Hadieh; Mohd Zain, Sharifuddin; Wan Abdullah, Wan Ahmad Tajuddin
<x xml:space="preserve">Abstract</x> The P-site-A76-2′OH transfers the polypeptide chain to the A-site α-amine and A2451 facilitates this transfer by acting as proton shuttle.